Answer:
D
Step-by-step explanation:
Using cosine formula, we have
The equivalence of the equation is 5x + 48 = 5x + 3.
Since 48 cannot be equal to 3, hence there are no solution.
<h3>What is the value of x?</h3>
Given the equation; x-4[ x - 2( x + 6) ] = 5x + 3
We remove the parentheses
x-4[ x - 2( x + 6) ] = 5x + 3
x-4[ x - 2x - 12 ] = 5x + 3
x - 4x + 8x + 48 = 5x + 3
5x + 48 = 5x + 3
We can go further and collect like terms
5x - 5x + 48 = 3
48 ≠ 3
Since 48 cannot be equal to 3, hence there are no solution.
Learn more about equations here: brainly.com/question/14686792
#SPJ1
Answer:
39.96/6=6.66
Do the long division
39/6=6 R3
Step-by-step explanation:
Answer:
20
Step-by-step explanation:
25 + 7x = 165
25 + 7(20) = 165
25 + 140 = 165
Answer:
12+36p
Step-by-step explanation:
First distribute the 2 to binomial then the 6.
6(2+6p)
12+36p